PLACEMENT OF CAPACITOR IN A RADIAL DISTRIBUTION SYSTEM USING LOSS SENSITIVITY FACTOR AND CUCKOO SEARCH ALGORITHM. (International Journal of Scientific Research and Management (IJSRM), 2017)
PLACEMENT OF CAPACITOR IN A RADIAL DISTRIBUTION SYSTEM USING LOSS SENSITIVITY FACTOR AND CUCKOO SEARCH ALGORITHM.